A Legitimidade institucional da estrutura regulatória brasileira pós-88 - Azevedo, Henrique Sampaio de (2017)
The central theme of this paper is the regulatory paradigm in post-88 Brazilian law and the process of justification of its legitimacy. Specifically, we investigate the theoretical basis from which the structure of independent regulatory agencies was interpreted and legitimized within the legal framework established by the Federal Constitution of 1988. Thus, The present work seeks to explore the evolution of the concept of the legitimacy of regulatory action, insofar as it adds different elements for the ratification of its own logic and structure. We first analyze the discussions about the legitimacy that is based only on its formal compatibility with the rule of law, that is, its conflicting nature with principles of legality and separation of powers. Furthermore, we study the efficiency argument, from which the whole regulatory system must be reinterpreted in order to promote specific goals and obtain good result. Later, the problem of the agencies' “democratic déficit” is reconstructed, from which their legitimacy should be extracted from models of popular participation, in order to close some kind of democratic gap. Finally, it’s presented an institutional model that considers itself able to couple different values present in the concept of democracy, making it ideal for dealing with the problema of regulatory legitimacy.